The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1997
DOI: 10.1001/archsurg.1997.01430280026003
|View full text |Cite
|
Sign up to set email alerts
|

Gastrointestinal Complications Following Cardiac Surgery

Abstract: Patients who have GI complications after cardiac surgery have a higher mortality and a longer hospital stay. The use of a left internal mammary artery seems to have a protective effect against GI complications. Based on these observations, patients may be stratified into low-, medium-, and high-risk groups.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
39
3

Year Published

2001
2001
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(44 citation statements)
references
References 21 publications
2
39
3
Order By: Relevance
“…Supporting our hypothesis, all these factors suggest why we observed no GIS complication in either study group. It has been reported that development of GIS complications in cardiac surgery is linked with postoperative mechanical ventilation, duration of stay in the ICU, and duration of hospital stay (12). There were no differences between our study groups concerning time to extubation or time of hospital stay.…”
Section: Discussioncontrasting
confidence: 45%
“…Supporting our hypothesis, all these factors suggest why we observed no GIS complication in either study group. It has been reported that development of GIS complications in cardiac surgery is linked with postoperative mechanical ventilation, duration of stay in the ICU, and duration of hospital stay (12). There were no differences between our study groups concerning time to extubation or time of hospital stay.…”
Section: Discussioncontrasting
confidence: 45%
“…Only 8 studies thus far used multivariate analysis to identify the independent determinants of GI complications in cardiac surgery. 3,7,[14][15][16][17][18][19] Although, the pathogenesis of GI lesions is complex and multifactorial, the major factor implicated in cardiac surgery is reduced systemic blood flow which is affected by multiple perioperative variables.…”
Section: Discussionmentioning
confidence: 99%
“…There are studies that favor that relationship, 14,16,18) and some that do not find a significant relationship. 15,17,19) In our analysis, although cardiopulmonary bypass (CPB) time and crossclamp time were higher in the GI complications group, they were not statistically significant both in univariate and multivariate analysis.…”
Section: Discussionmentioning
confidence: 99%
“…Upper gastrointestinal bleeding (UGIB) remains an important complication following cardiac surgery since, although infrequent, these complications are clinically relevant because of their associated mortality [1]. Many GI complications are reported, with only few studies addressing specifically upper GI bleeding in this context [1][2][3].…”
Section: Introductionmentioning
confidence: 99%
“…Many GI complications are reported, with only few studies addressing specifically upper GI bleeding in this context [1][2][3]. Moreover, the generalizability of past study findings is limited by differences between the supportive cares administered over a decade ago versus today.…”
Section: Introductionmentioning
confidence: 99%